2022
DOI: 10.3390/su14105971
|View full text |Cite
|
Sign up to set email alerts
|

Applying Marine Protected Area Frameworks to Areas beyond National Jurisdiction

Abstract: Marine protected areas (MPAs) can provide a range of ecological benefits. Frameworks—including the IUCN protected area categories and The MPA Guide—offer tools towards evaluating an MPA’s objectives, types, Level of Protection, and potential effectiveness. However, the majority of MPAs exist in national waters, raising the question of how these frameworks apply in areas beyond national jurisdiction (ABNJ). We evaluated the existing ABNJ MPAs in the Antarctic designated through the Commission for the Conservati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…For example, the International Union for the Conservation of Nature (IUCN) defines an MPA as: "a clearly defined geographical space, recognized, dedicated and managed, through legal or other effective means, to achieve the long-term conservation of nature with associated ecosystem services and cultural values" 30 . The reference to "long-term" in the definition is often thought to allude to the idea that an MPA should exist in perpetuity, though others refer to long-term as existing longer than 10 years 18,31,32 . After much negotiation as to whether the definition of an MPA should include reference to duration, the BBNJ Agreement defines an MPA as: "a geographically defined marine area that is designated and managed to achieve specific long-term biological diversity conservation objectives and may allow, where appropriate, sustainable use provided it is consistent with the conservation objectives" 17 .…”
Section: Precedent Settingmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, the International Union for the Conservation of Nature (IUCN) defines an MPA as: "a clearly defined geographical space, recognized, dedicated and managed, through legal or other effective means, to achieve the long-term conservation of nature with associated ecosystem services and cultural values" 30 . The reference to "long-term" in the definition is often thought to allude to the idea that an MPA should exist in perpetuity, though others refer to long-term as existing longer than 10 years 18,31,32 . After much negotiation as to whether the definition of an MPA should include reference to duration, the BBNJ Agreement defines an MPA as: "a geographically defined marine area that is designated and managed to achieve specific long-term biological diversity conservation objectives and may allow, where appropriate, sustainable use provided it is consistent with the conservation objectives" 17 .…”
Section: Precedent Settingmentioning
confidence: 99%
“…For example, Edgar et al 18 states that MPAs are considered "old" when they have been in existence for 10 years or longer, while Claudet et al, 35 found that duration of the MPA matters less than the size and location of the MPA. Thus, the 35-year duration of the Ross Sea region, coupled with its location and objectives, likely qualifies it as an MPA 32,36 .…”
Section: Precedent Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Areas beyond national jurisdiction (the high seas) cover nearly two thirds of the ocean surface and ∼90% of the ocean volume on Earth (Visalli et al., 2020; Nocito et al., 2022). The high seas support an extreme abundance and diversity of life, global nutrient cycles, carbon sequestration, climate regulation, fisheries, tourism, and other economic activities (Rochette et al., 2014; Popova et al., 2019).…”
Section: Introductionmentioning
confidence: 99%